Adsorpsi Ion Amonium dari Larutan Encer Menggunakan Zeolit Alam Sarulla Termodifikasi KCl - Husin, Amir; Harahap, Hamidah; Ansari, Wan Rizki; Supriharti, Denny; Fadhila, Fadhila (Jurnal Teknik Kimia USU, 2025)
This study aims to evaluate the effectiveness of KCl-modified Sarulla natural zeolite in removing ammonium ions from aqueous solutions. The zeolite was modified by soaking in 0.5 M (ZA05) and 1.5 M (ZA15) KCl solutions for 24 hours at a solid/solvent ratio of 1:3 (weight/volume). The adsorption process was conducted in batch mode using an orbital shaker at a speed of 100 rpm, with contact times ranging from 0 to 210 minutes. The initial ammonium ion concentration was 100 mg/L, and the analysis was performed using a UV-visible spectrophotometer. The results showed that ZA05 and ZA15 adsorbents achieved ammonium ion removal efficiencies of 14.62% and 12.29%, respectively. Adsorption isotherm analysis using the Langmuir and Freundlich models demonstrated a good fit with the equilibrium data, with ZA15 exhibiting a higher maximum adsorption capacity than ZA05. This study confirms the potential of KCl-modified Sarulla natural zeolite as an effective adsorbent material for wastewater treatment.